The economy of sustainable construction. - (:unkn) unknown (Ruby Press, 2014)
Sustainability s greatest obstacle is financial. Investors and developers blame noncompliance with sustainability standards on the supposedly higher costs and lower profits of sustainable construction. But with rapid urbanization, a sluggish economy, and a worsening climate crisis, we urgently need more sustainable construction practices and buildings. The Economy of Sustainable Construction seeks to dispel the myth that sustainability cannot be profitable, evaluate current architectural practices and models, and introduce materials and methods to maximize the environmental, social, and economic performance of buildings. Essays, reports, and case studies examine the relationship between commercial and sustainable values and explore the paths that construction will take in the twenty-first century.
Keywords: Bebauung; Bautechnik; Gebäude; Ökologisches Bauen; Wirtschaftlichkeit; Finanzierung; Dichte; Urbanität; Stadtstruktur; Leitbild; Industrieland; Entwicklungsland; Beispielsammlung; Nachhaltigkeit; Resilienz; Stadtumbau